Multispecies reactor design for fluorination reduction of lunar regolith - Maharaj, Riddhi Anubhav (Department of Electrical Engineering, 2025)
Citronellal was converted over sulphonated polystyrene resin catalysts of different acid loading. The catalysts had been prepared sulphonating a commercial polystyrene resin with sulfuric acid. Catalyst activities were screened in the liquid phase and in the gas phase in a temperature range of 50 to 110 oC, varying space velocity. Catalyst activities (in terms of rates of citronellal conversion) followed the degree of sulphonation and were similar in both the environments, but apparently governed by external mass transfer control in the liquid phase or limited by the very low partial pressure of citronellal in the gas phase. No effect of the degree of sulphonation on selectivity was observed.